Characteristics of a Compact Circularly Polarized Microstrip Antenna - Gupta, V. R.; Gupta, N. (Elektronika ir Elektrotechnika, 2004)
A novel compact circular polarization (CP) operation of a microstrip antenna with four semicircular grooves along the four edgesof the patch and a pair of truncated corners is proposed and investigated. The simulation is performed using Zeland IE3D, an integratedfull wave electromagnetic simulation and optimization package for the analysis and design of three dimensional microstrip patchantennas. The simulation results show that the proposed compact CP design can have an antenna size reduction as compared to theconventional corner truncated square microstrip antenna at a given operating frequency. Details of the design considerations of theproposed antenna are described, and simulation results of the obtained CP performance are presented and discussed. Ill. 4, bibl. 4 (inEnglish; summaries in Lithuanian, English and Russian).